Notes mozabites - Schacht, Joseph (Al-Andalus, 1957)
On Ibāḍī mosques in Ouargla, Mīzāb and at Jerba (with plans and photographs), on Ibāḍī cemeteries in Mīzāb, on style in Ibāḍī architecture, and finally some observations on “modernism and the movement of sheikh Ibr. Bayyūḍ” and on education in Mīzāb.
Keywords: Architecture -- Mzab; Ghuraba, mosquée al- (Houmt Souk, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Monuments -- Djerba; Shaykh, mosquée al- (Houmt Souk, Djerba)

Sur la diffusion des formes d’architecture religieuse musulmane à travers le Sahara - Schacht, Joseph (Travaux de l'Institut de Recherches Sahariennes, 1954)
Keywords: Architecture -- Djerba; Ghuraba, mosquée al- (Houmt Souk, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Monuments -- Djerba; Shaykh, mosquée al- (Houmt Souk, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba)

L'artisanat traditionnel dans le département d'Alger et le territoire de Ghardaïa - Schacht, Joseph (Documents algériens, 1953)
Keywords: Artisanat -- Mzab

Bibliothèques et manuscrits Abadites - Schacht, Joseph (Revue Africaine, 1956)
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Bibliothèques -- Djerba; Bibliothèques -- Mzab; Manuscrits -- Djerba; Manuscrits -- Mzab

An Unknown Type of Minbar and Its Historical Significance - Schacht, Joseph (Ars Orientalis, 1957)
Keywords: Ghuraba, mosquée al- (Houmt Souk, Djerba); Monuments -- Djerba